Abordagem teórica do processo de geração de biometano a partir de resíduos agroindustriais - Silva, Cristine Brandt da (2017)
Renewable energy generation challenges companies to engage in a chain process in which all links are co-responsible for the generation of new products, processes and responsible consumption and production, protecting the environment and improving the lives of people with whom Interactions. The present research aimed to propose a theoretical approach of the biomethane generation process from agroindustrial waste. For the accomplishment of the theoretical approach, a Bibliographic Portfolio was constructed and techniques of systematic literature reviews were adopted to ensure that recent and relevant studies on the research topic were captured. The theoretical approach was divided into three main phases, and the first phase of the biomethane generation process included the selection, pretreatment and transport of the organic material to the biodigester. The second phase of the process included decisions such as the choice of biodigester model and the final use of biofertilizer and biogas generated. Finally, the third phase of the biomethane generation process included decisions such as the choice of technology to be used for the purification process and the final use of biomethane. The process of generating biomethane from agro-industrial waste is a subject of few publications in Brazil. The use of biomethane in countries such as Germany, the United Kingdom and Sweden is at a considerably advanced stage compared to legislation and technologies compared to Brazil. Thus, the proposal of this study assists academics, researchers and managers, in understanding the process as a whole and in making sustainable decisions.